2008
DOI: 10.1055/s-0039-1697384
|View full text |Cite
|
Sign up to set email alerts
|

Styloid Process Elongation or Eagle’s Syndrome: Is There Any Role for Ectopic Calcification?

Abstract: The styloid process (SP) is a cylindrical, long cartilaginous bone located on the temporal bone. The normal SP length is approximately 20–30 mm. The styloid process elongation (SPE) can be assumed if either the SP or the adjacent stylohyoid ligament ossification shows an overall length in excess of 30 mm. Elongated SP is known as Eagle’s syndrome when it causes clinical symptoms as neck and cervicofacial pain. It is supposed that this symptoms and signs are due to the compression of the SP on some neural and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
24

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 44 publications
2
50
0
24
Order By: Relevance
“…Putative normal length and prevalence values on previous studies are shown in Table 8. Prevalence of elongated SHC varies between 4.5% and 63.2% in studies which proposed 30 mm as normal length [5,13,18,22,28,30,35,37,40]. Andrei et al [1] determined the normal length of SHC as 35 mm and they reported the prevalence of elongated SHC as 40% in their CBCT study.…”
Section: Discussionmentioning
confidence: 99%
“…Putative normal length and prevalence values on previous studies are shown in Table 8. Prevalence of elongated SHC varies between 4.5% and 63.2% in studies which proposed 30 mm as normal length [5,13,18,22,28,30,35,37,40]. Andrei et al [1] determined the normal length of SHC as 35 mm and they reported the prevalence of elongated SHC as 40% in their CBCT study.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need to take informed consent, because the data was evaluated retrospectively. (Prasad et al, 2002;Carter, 2004;Jung et al, 2004;Gokce et al, 2008).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The reason for SPE is not clear (Gokce et al, 2008). It has been suggested that neighboring chronic irritation, surgical injury, endocrine changes in females at menopause, development of the bony tissue, and mechanical anxiety or injury during the development of the SP could bring about calcified hyperplasia of the SP (Balbuena et al, 1997;Fini et al, 2000;Prasad et al, 2002;Gokce et al, 2008).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Eagle syndrome (ES) which is also known as styloid-carotid artery syndrome, is a rare condition with an elongation of SP or calcification of stylohyoid ligament and clinical symptoms such as neck and cervicofacial pain (1)(2)(3)(4)(5)(6)(7). It was first described by an otorhinolaryngologist, whose name was Eagle, in 1937 (8).…”
Section: Introductionmentioning
confidence: 99%